(untitled) (Contemporary Mathematics, 2023)
Linearized polynomials are gaining attention from many researchers because of their applications in the field of coding theory, cryptography and finite geometry. The linearized polynomials of the type Tlk (Z) and Slk (Z) were recently introduced in the literature. The characterization of these linearized polynomials and patterns in their roots over finite fields have been extensively studied by various authors. In the present paper, we extend the study of families of linearized polynomials Tlk (Z) and Slk (Z) by taking k and l as prime powers and construct new families of linearized polynomials over finite fields. Further, we establish relation between linearized polynomials Tlk (Z) and Slk (Z) which may be helpful in determining zeros of these polynomials over finite fields.